Ketidakadilan dalam Penegakan Hukum di Indonesia: Sebuah Tinjauan Kritis - Deni Dwi Firmansyah; Elza Qorina Pangestika (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
Fair law enforcement is a fundamental principle in the legal system of any country, including Indonesia. However, in practice, injustice often occurs in the law enforcement process in Indonesia, which can lead to discrimination, abuse of power, and unequal access to justice. This article aims to examine the factors that cause injustice in law enforcement in Indonesia and its impact on society and the legal system. Key factors contributing to injustice include corruption within law enforcement agencies, unequal access to justice, dysfunction in legal institutions, political influence in legal processes, and an authoritarian legal culture. The consequences are significant, including the erosion of public trust in the legal system, abuse of power, and increased social inequality. Therefore, this article offers several solutions, such as eradicating corruption, improving access to justice, and reforming the legal culture and law enforcement system in Indonesia. A systematic and comprehensive effort is needed to create a fairer and more equitable law enforcement system for all layers of Indonesian society.